Investigating the Effect of Green Accounting Adoption and Sustainability Disclosure in Indonesian Manufacturing Companies - Adisty, Tri Julian; sumarna, alfonsa dian (Journal of Applied Accounting and Taxation, 2025)
Companies currently produce many impacts, such as air pollution and industrial waste, which also cause global warming. As part of the company's responsibility for international and sustainability problems, the company carries out several things related to green things, ultimately leading to company profits. This research examines the effect of green accounting and sustainability disclosure on company profitability. The sustainability disclosure includes economic, environmental, and social indicators. The population in this study are manufacturing companies listed on the Indonesia Stock Exchange in 2019-2022. Researchers selected the sample using a purposive sampling method with three criteria, resulting in 15 eligible companies. This research uses panel data regression analysis using the Eviews 12 program. This research measures the green accounting variable using PROPER, the sustainability disclosure variable using GRI G4, and the profitability variable using ROA. The analysis results show that the green accounting and sustainability disclosure variables do not affect a company's profitability. Indonesia has required the disclosure of sustainability reports for specific companies, including those used in this research. Even though there are mandatory regulations, there are still several challenges in implementing sustainability reporting in Indonesia. For example, a lack of awareness and varying reporting standards. The obligation to prepare sustainability reports is an essential step for Indonesia in realizing sustainable development. A sustainability report hopes to encourage companies to be more responsible for the environment and society while increasing global competitiveness and making a profit.